Epigenetic Regulation of Tumor Suppressors by Helicobacter pylori Enhances EBV-Induced Proliferation of Gastric Epithelial Cells - Saurabh Pandey; Hem Chandra Jha; Sanket Kumar Shukla; Meghan K. Shirley; Erle S. Robertson (mBio, 2018)
ABSTRACT Helicobacter pylori and Epstein-Barr virus (EBV) are two well-known contributors to cancer and can establish lifelong persistent infection in the host. This leads to chronic inflammation, which also contributes to development of cancer. Association with H. pylori increases the risk of gastric carcinoma, and coexistence with EBV enhances proliferation of infected cells. Further, H. pylori-EBV coinfection causes chronic inflammation in pediatric patients. We have established an H. pylori-EBV coinfection model system using human gastric epithelial cells. We showed that H. pylori infection can increase the oncogenic phenotype of EBV-infected cells and that the cytotoxin-associated gene (CagA) protein encoded by H. pylori stimulated EBV-mediated cell proliferation in this coinfection model system. This led to increased expression of DNA methyl transferases (DNMTs), which reprogrammed cellular transcriptional profiles, including those of tumor suppressor genes (TSGs), through hypermethylation. These findings provide new insights into a molecular mechanism whereby cooperativity between two oncogenic agents leads to enhanced oncogenic activity of gastric cancer cells. IMPORTANCE We have studied the cooperativity between H. pylori and EBV, two known oncogenic agents. This led to an enhanced oncogenic phenotype in gastric epithelial cells. We now demonstrate that EBV-driven epigenetic modifications are enhanced in the presence of H. pylori, more specifically, in the presence of its CagA secretory antigen. This results in increased proliferation of the infected gastric cells. Our findings now elucidate a molecular mechanism whereby expression of cellular DNA methyl transferases is induced influencing infection by EBV. Hypermethylation of the regulatory genomic regions of tumor suppressor genes results in their silencing. This drastically affects the expression of cell cycle, apoptosis, and DNA repair genes, which dysregulates their associated processes, and promotion of the oncogenic phenotype.